Empowering women through handicrafts training from plastic waste at the Bungaeja community learning center - Hastuti, Hastuti; Zulfida, Wa Ode; Revika, Revika; Syalman, Syalman (Community Empowerment, 2021)
The purpose of this community service program is to provide skills in making handicrafts with household waste raw materials, distributing or marketing handicrafts. The methods used were mentoring, training, and direct practice. The training achievement was that participants have skills in processing plastic waste and used bottles so that they have more economic value. In addition, empowerment participants have high creativity in creating more varied products.